The effect of current on coral growth form in selected areas of Tioman Island, Pahang - Halid, Nor Hidayah; Ahmad, Zuhairi; Kamarumtham, Kharina; Saad, Shahbudin; Khodzori, Mohd Fikri Akmal; Muhammad Hanafiah, Muhammad Faiz; Yusof, Muhamad Hamizan (Universiti Malaysia Sabah, 2016)
Current is a prominent event in the ocean and one of the significant factors that determine the construction of the reef ecosystem. Each individual reef has its unique growth form and the distribution is influenced by current in the particular localities. Interrelation between current and morphological response of coral growth was studied in selected location at Tioman Island. Acoustic Doppler current profile (ADCP) was deployed to collect data of current speed and current direction. MIKE 21 Flow model FM software was used to model the hydrodynamic pattern of the study area. The model was calibrated using secondary field current data with reasonable R2 value of 0.6096. Using the calibrated model, the mean current speed for two selected stations at the West coast of Tioman Island was 0.035 ms-1 and 0.172 ms-1; while the mean current speed for two selected stations at the East coast of Tioman Island was 0.030 ms-1 and 0.050 ms-1. Based on the coral growth form distribution at the study area, the type of growth forms at the west coast dominated by ACD and CM coral while in the east coast was dominated by ACD and CP coral respectively. Different growth forms of coral were emerged in response to different current speed. This study showed the distribution of coral growth forms were influenced by the current action.